Risk Assessment Study of Oil Flow Under Inrush Current on the Misoperation of Converter Transformer Gas Relay - Wenhao He; Zhanlong Zhang; Yu Yang; Jiatai Gao; Xichen Pei; Jun Deng; Zhicheng Pan; Jinzhuang Lv; Hongliang Yao (Applied Sciences)
In practical engineering, due to the residual magnetism in the iron core of the converter transformer, the inrush current is generated in the case of no-load closing, and the inrush current leads to an oil flow surge inside the converter transformer. Under the influence of oil flow, the gas relay plate will be deflected, and when the deflection angle is too large, the gas relay will malfunction. Because of the lacking research on the influence of the misoperation of the gas relay under the excitation inrush of the converter transformer, it is difficult to effectively suppress the misoperation of gas relay under inrush current. Therefore, the finite element model of the electromagnetic hydraulic coupling of the converter transformer is established in this paper to obtain the oil flow velocity through the gas relay under the inrush current. A fluid–solid coupling model was established inside the gas relay to study the deflection characteristics of the baffle of the gas relay under the inrush current, and the relationship between the inrush current amplitude and the deflection angle of the baffle was mathematically fitted to effectively predict whether the gas relay has the risk of misoperation. From the experimental results, it can be seen that when the amplitude of the inrush current exceeds 6.37 kA, the gas relay will have the risk of misoperation. Finally, the influence of oil flow impact on the gas relay baffle under multiple cycles is considered. The results can provide an effective reference for analyzing the diagnosis of gas relay misoperation under the effect of inrush current.